Fungsi dan Peranan Tinggalan Arkeologi di Pura Yeh Gangga Desa Perean Kabupaten Tabanan - Ary Purwaningsih, Komang; Aryana, A.A Gde; Palupi Titasari, Coleta (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
Title the study is Function and Roles of the archaeological heritage in Yeh Gangga Temple Tabanan Regency has the aim knowing the function of archaeological heritage and roles of archaeological heritage for the society Perean Village. Data in this study were obtained by using observation, interview, and literature techniques and then the data were analyzed using qualitative analysis, contextual analysis, and comparing analysis. As a result of the study, it was found that the function archaelogical heritage in Yeh Gangga Temple has a manifestation God to keep safety, prosperity, pacify, healty and fertility, while roles of the archaeological heritage in Yeh Gangga Temple in social aspect has media to unite society of Perean Village, in the cultural aspect field it would be one tengible evidence of mixing process between the culture of Java and Bali, and then pride for society Perean Village, in religious field the archaeological heritages functions as the media of maintaining a good relationship between the local community with the ancestors and Gods.